Bosnia & Herzegovina : Economic Mobility, Jobs and Gender - Davalos, Maria Eugenia (World Bank, Washington, DC, 2018)
The aim of this case study is to qualitatively assess men and women's perceptions of economic mobility, access to labor market and entrepreneurship opportunities, and the impact of selected labor market and social assistance policies. Through the use of focus group discussions and semi-structured interviews, the study aims to uncover underlying differences in perspective by gender, related to the main study topics. The study is structured along four main themes: (1) economic mobility and shared prosperity; (2) pathways and barriers to employment; (3) youth transitions, and (4) coping with poverty and joblessness.